2009
DOI: 10.1016/j.chom.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Interferes with Host Cell Motility by Deregulation of Cofilin

Abstract: HIV-1 Nef is a key factor in AIDS pathogenesis. Here, we report that Nef potently inhibits motility of fibroblasts and chemotaxis of HIV-1-infected primary human T lymphocytes toward the chemokines SDF-1alpha, CCL-19, and CCL-21 ex vivo. Furthermore, Nef inhibits guided motility of zebrafish primordial germ cells toward endogenous SDF-1a in vivo. These migration defects result from Nef-mediated inhibition of the actin remodeling normally triggered by migratory stimuli. Nef strongly induces phosphorylation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
171
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(187 citation statements)
references
References 60 publications
(67 reference statements)
10
171
1
5
Order By: Relevance
“…La protéine virale Nef est capable de modifier le cytosquelette d'actine des lymphocytes T et, ainsi, leur migration [7]. Nous avons donc étudié l'effet de Nef sur la structure d'actine principale des macrophages : les podosomes.…”
Section: La Protéine Nef Du Vih-1 Cible Les Podosomes Et Contrôle Ainunclassified
See 3 more Smart Citations
“…La protéine virale Nef est capable de modifier le cytosquelette d'actine des lymphocytes T et, ainsi, leur migration [7]. Nous avons donc étudié l'effet de Nef sur la structure d'actine principale des macrophages : les podosomes.…”
Section: La Protéine Nef Du Vih-1 Cible Les Podosomes Et Contrôle Ainunclassified
“…Dans un travail récent [2], nous avons montré in vitro que l'infection des macrophages humains par le VIH-1 inhibe leur migration en 2D et leur migration 3D amiboïde mais que, en revanche, le mode migratoire mésenchymateux est stimulé. Dans le cas des lymphocytes T CD4, qui migrent uniquement selon le mode amiboïde, l'infection inhibe leur migration [1,7]. C'est la protéine virale Nef, un facteur de virulence majeur du VIH-1, qui reprogramme à la fois la migration des cellules T [7] et celle des macrophages [2] (Figure 1).…”
Section: La Protéine Nef Du Vih-1 Cible Les Podosomes Et Contrôle Ainunclassified
See 2 more Smart Citations
“…The mammalian cofilin-1 is the most ubiquitous and involved in viral infection. HIV-1 inactivates cofilin to optimize immune evasion, replication, release, and cell-cell transmission [19,20,21]. We have previously reported that cofilin-1 play a crucial role in mediating biphasic F-actin dynamics to facilitate HSV-1 infection and replication [22,23].…”
Section: Introductionmentioning
confidence: 99%